Death simulation behavior of the lizard Lygodactylus klugei of the Gekkonidae (Reptilia: Squamata) family in northeastern Brazil - Matias, Cicera Silvilene Leite; de Araújo, Danilo Saraiva; de Castro, Deborah Praciano (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
Natural selection favors primary defense strategies that reduce the chance of prey being spotted and discovered by a potential predator, such as camouflage, aposematism, and secondary defense strategies that include tail loss and escape, immobility, and thanatosis. The behavior of thanatosis (playing dead) or tonic immobility (body paralysis) is a strategy adopted by the prey, in which the animal simulates immobility to avoid being ingested. This simulation is effective against visually oriented predators or predators that do not feed on dead prey. Belonging to a complex of cryptic species, Lygodactylus klugei is a gecko that has a wide distribution in Northeast Brazil, occupying areas of the Caatinga and Cerrado, and that has a diurnal habit. On August 25th and September 2nd, 2021, three individuals of L. klugei were observed exhibiting thanatosis behavior during plant suppression work in the Curaçá municipality, Bahia state, Brazil. This behavior is reported for the first time in for L. klugei, and the species may use it if it is unable to escape from visually oriented predators. However, we suggest that future observations may generate new hypotheses about the benefits of this behavior in the species. Our observation adds important data to the behavioral repertoire of lizards from the Gekkonidae family, providing important natural history data to try to understand the defense mechanisms adopted by lizards in general.
Keywords: Defense strategies; Natural selection; Predation; Reptiles; Thanatosis